The influence of thinking styles and gender on students' creative thinking abilities in physical education - Dupri; Suherman, Adang; Budiana, Dian; Juliantine, Tite (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2024)
Background: Modern developments require Generation Z to be able to face future challenges that cannot be predicted. Research Objectives: The purpose of this study is to investigate how thinking styles and gender can develop creative thinking skills in students when learning physical education and also to investigate the interaction between thinking style and gender on creative thinking skills. Methods: This study used a non-experimental design. Thinking style is measured by learning and thinking style tests (SOLAT), and creative thinking skills are measured by the Torrance Test of Creative Thinking (TTCT), which consists of four indicators: fluency, flexibility, originality, and elaboration. The sampling technique in this study was cluster random sampling. The random process is carried out in two stages: the first is random selection by randomly selecting, and the second is the second is random assignment. The sample for this research was 68, consisting of 33 men and 35 women. Meanwhile, the analysis was done by looking at n-gain and continuing with the ANOVA test. Findings/Results: The results of this study indicate that thinking styles and gender significantly impact students' creative thinking ability, and there is also an interaction between thinking styles and types that significantly affects students' creative thinking ability. The analysis of the data obtained found a significant relationship between gender and students' creative thinking skills in physical education. Conclusion: Male students have better creative thinking skills than female students because they tend to use the right brain to develop their thinking skills. In developing creative thinking skills, grouping based on gender is necessary. Future research needs to be conducted by considering the right learning model for developing creative thinking skills during physical education learning.